HUMAN CAPITAL FACTORS IN ENCOURAGING NON-FINANCIAL PERFORMANCE OF CREATIVE INDUSTRIES STUDY AT THE CIBADUYUT SHOES CENTER OF BANDUNG CITY-WEST JAVA-INDONESIA (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine the role of human capital and nonfinancial performance in the creative shoe industry in Cibaduyut, Bandung, West Java, Indonesia. The research methods used are descriptive and verification, primary data, validity test data, reliability and classical assumptions, a population of 80 company units and 152 samples of workers / trips. To test the contribution of factors used Confirmatory Factor Analysis and the coefficient of determination The results showed that there were four (4) dominant factors of human capital that determined the creative industry of Cibaduyut shoes, namely 1) Individual potential and personality, 2) Training Program, 3) Competency and 4) Family, with a contribution of 76.06%, while for performance nonfinancial are 1) Capital requirements and government policies for the shoe business are currently very supportive with a contribution of 58.68%.